Korean red ginseng extracts alleviate skin damage in heat-stimulated skin cells by suppressing NF-κB activation - Kim, Jeeyoung; Bang, Weon Jeong; Joo, Yung Hyup; Lee, Sung Hyun; Lee, Chang-Seok (Archives of Biological Sciences, 2025)
Paper description: Red ginseng extract (RG) contains ginsenosides, gintonins, and polypeptides, and exhibits anti-aging, immunomodulatory, and anti-inflammatory properties. In vitro studies examined the recovery effects of RG on skin damage caused by heat-induced barrier disruption, aging, and inflammation. RG alleviated skin barrier damage. Nuclear factor kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) pathways were activated by heat stimulation, but only NF-κB activation was suppressed by RG treatment. RG restores and alleviates skin damage. Abstract: This study explored the impact of heat stimulation on skin barrier damage, aging, and inflammatory responses by analyzing gene and protein-level changes. Additionally, it examined the restorative effects and regulatory mechanisms of red ginseng (RG) extract. The results demonstrated that heat stimulation decreased mRNA expression of the skin barrier markers, aquaporin 3 (AQP3), ceramide synthase 3 (CerS3), and occludin (OCL), while increasing the expression of matrix metalloproteinases (MMP)-1, MMP-2, and MMP-3, and proinflammatory factors such as interleukins IL-6 and IL-8, which are associated with skin damage. RG treatment modulated the expression of disrupted skin barrier markers (AQP3, CerS3, OCL), aging markers (MMP-1, -2, -3), and inflammatory factors (IL-6, IL-8), confirming the recovery-promoting effects against heat-induced skin damage. Mechanistic analysis revealed that both nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) pathways were activated by heat stimulation, with NF-κB activation suppressed by RG treatment. In conclusion, RG demonstrated the ability to restore skin integrity and alleviate damage.